Cultural Acculturation in the Landlord Family Residence in Kampung Kulitan Semarang - Sukawi, Sukawi; Hardiman, Gagoek; Rukayah, Raden Siti (MODUL, 2023)
Kampung Kulitan is located in the Jagalan area, Central Semarang. This village is the forerunner of the Tasripin Kingdom which holds high historical value. The historical value is the Tasripin family home that has not been changed or renovated since its inception. Formerly Tasripin was the one who controlled the land in the Kampung Kulitan area. These houses are historical evidence of the glory of Semarang in the past. To protect the historical value of Kampung Kulitan, Semarang City Government has established the village as a tourist village with the theme of the old village with the Tasripin family house which became the cultural heritage asset in Kampung Kulitan. This study aims to determine how much influence the indis architecture has on the facade appearance of buildings in Kampung Kulitan. This study used descriptive qualitative method. Data collection is done using observations in the field. Observations on objects are supported by interviews with homeowners or other sources who are aware of the development of Kampung Kulitan residential area. The results of data collection are analyzed with the theories concerned about the indis architecture and the appearance of the building. The results of this study indicate that cultural acculturation has occurred, especially the Indis architecture in the form of building facades in Kampung Kulitan. This makes housing in Kampung Kulitan very unique and requires accuracy in its rehabilitation.